Angola : Second Review of the Extended Arrangement Under the Extended Fund Facility, Requests for a Waiver of Nonobservance of Performance Criteria, Modifications of Performance Criteria, and Financing Assurances Review-Press Release; Staff Report; and Statement by the Executive Director for Angola. (IMF Staff Country Reports; Country Report ;, 2020)
The economic outlook has deteriorated since the First Review. Real GDP is expected to contract in 2019, driven by lower-than-expected oil production. Disinflation is expected to halt, inter alia because of increases in regulated prices. Beyond 2019, lower oil prices and slower recovery in oil production are expected to weigh on oil exports and put pressure on the external current account and international reserves. While the rapid depreciation of the exchange rate has led to a sizable increase in the debt-to-GDP ratio, the ongoing fiscal retrenchment will help shield public expenditure from oil-price volatility and reverse the public debt trend.